Life with wildlife: from princely India to the present - Ranjitsinh, M.K. (Noida Harper Collins, 2017)
A Life with Wildlife traces the course of wildlife from the princely and British era to the present and shows how wildlife conservation efforts in India have always emanated from the upper echelons of power.
Keywords: Wildlife